The Effect Of Work Discipline, Organizational Commitment and Competency On The Performance Of Novotel Pekanbaru Hotel Employees - Karima, Nadia; Ningsih, Dewita Suryati; Rifqi, Ahmad; Fitriani, Arika (Program Pascasarjana, Universitas Riau, 2023)
This study aims to determine the effect of work discipline, organizational behavior and competence on employee performance. This research was conducted at the Novotel Hotel Pekanbaru. The research population in this study was the Novotel Hotel employees as many as 135 people. The research sample was taken as many as 57 people using the Slovin formula with a total sample of 57 people. The data collection method used in this study was a questionnaire about work discipline, organizational behavior and performance competence and then analyzed using multiple linear regression. The results of this study are (1) there is a significant effect of work discipline on employee performance. This means that the higher the employee's work discipline, the higher the performance of the Novotel Pekanbaru Hotel employees. (2) there is an effect of organizational commitment on employee performance. This means that the higher the employee's organizational commitment, the higher the performance of the Novotel Pekanbaru Hotel employees. (3) there is an influence of employee competence on the performance of Novotel Hotel employees. This means that the higher the competence of employees, it can improve employee performance. (4) Simultaneously, there is a significant influence between work discipline, organizational commitment, and employee competence on the performance of Novotel Pekanbaru Hotel employees.